Frequency and factors associated with delay in breast cancer treatment in Brazil, according to data from the Oncology Panel, 2019-2020 - Mário Círio Nogueira; Adriana Tavares de Moraes Atty; Jeane Tomazelli; Beatriz Cordeiro Jardim; Maria Teresa Bustamante-Teixeira; Gulnar Azevedo e Silva (Ministério da Saúde do Brasil, 2023)
Abstract Objective: to analyze treatment delay and the flow of care for women with breast cancer in Brazil in 2019 and 2020. Method: this was a follow-up study of breast cancer cases available from the Oncology Panel; a chi-square test and multilevel logistic regression were performed in order to analyze the explanatory variables associated with delay (greater than 60 days) in starting treatment. Results: 22,956 cases (54.5%) with delay in treatment were identified in 2019 and 17,722 (48.7%) in 2020; the Southeast region (54.6%) had the greatest proportion of delay; delay was greater when treatment was provided outside the municipality of residence and lower in 2020 compared to 2019; most outward flows were to the capital cities in the same Federative Units of residence. Conclusion: strategies to reduce cancer treatment delay and optimize health care networks in the Federative Units should be prioritized.